Insecure Attachment to God and Interpersonal Conflict - Jordan, Kevin D. (Religions, 2021)
Research has expanded the notion of attachment to caregivers to other figures such as God, and there is now literature supporting positive effects of attachment to God with various psychosocial outcomes. The dimensions of attachment to God—anxiety and avoidance—reflect varying ways that people see God as supportive and reliable versus unsupportive and inconsistent. As a stable aspect of the individual, attachment to God results in recurring patterns of interpersonal behavior that can maintain and support self-control or disrupt it. No studies have examined the moderating effect of attachment to God on the relationship between self-control and negative social exchanges. To fill this gap, a sample of 1049 adults across the United States completed measures on attachment to God, self-control, and interpersonal outcomes. First, results showed that insecure attachment to God is associated with a hostile-dominant interpersonal style. Second, it was found that the highest level of negative social exchanges occurred in individuals low in self-control and high in attachment avoidance and anxiety. Results are discussed in terms of self-regulation, stress exposure, and situation selection. An implication of the current study is that secure attachment to God may foster less stress exposure by influencing a person’s situation selection.